Late acceleration of glomerular filtration rate decline is a risk for hemodialysis catheter use in patients with established nephrology chronic kidney disease care. Issue 3 (5th December 2014) - Chin, Andrew I.; Nguyen, Tuan A.; Dinesh, Kumar P.; Morfin, José A.
Abstract Chronic kidney disease (CKD) patients with established nephrology care have a high rate of tunneled dialysis catheters (TDC) as first vascular access when transitioning to hemodialysis (HD). We sought to identify factors associated with this problem. Patients who started HD and had prior CKD care within our renal clinic were categorized according to access type at incident HD. Clinical factors, all estimated glomerular filtration rates (eGFR), renal clinic attendance records, hospital admissions in the 6 months preceding HD start, and patient participation in predialysis education course were analyzed. Three hundred thirty‐eight patients initiated HD, 107 received pre‐HD CKD care within our clinics. Seventy patients started with a TDC. All groups started HD at similar eGFR values. The trajectory of eGFR decline in the 6 months prior to HD start was significantly more rapid in the TDC group. Patients in the TDC group had more acute health events in the prior 6 months. Multivariate modeling showed that failure to attend a predialysis education course and having a more rapid rate of eGFR decline in the 6 months prior to dialysis initiation were both associated with TDC use. Patients with CKD nephrology care who initiated HD with a TDC as first vascular access had a more rapid rate of decline in eGFR in the months preceding dialysis start and were less likely to have attended our predialysis education course. This appears to correspond with the observed increased number of emergency and hospital visits in the 6 months prior to end‐stage renal disease.